Perceived Beneficiary of Employee Development Activity: A Three-Dimensional Social Exchange Model - Maurer, Todd J.; Pierce, Heather R.; Shore, Lynn M. (Academy of Management Review, 2002)
We present a model of employee decision making and behavior in which employees may sometimes decide to pursue learning and development activities, depending on personal values, leader-member exchange, perceived organizational support, self-efficacy for development, and credibility of information source. Within a three-dimensional “perceived beneficiary” system, employees may perceive these activities to benefit not only themselves but also (or alternatively) a supervisor and/or the organization. We show connections involving prosocial organizational behavior and organizational citizenship behavior and offer five propositions.